Ion absorption, distribution and salt tolerance threshold of three willow species under salt stress - Ran, Xin; Huang, Xiaoxi; Wang, Xiao; Liang, Haiyong; Wang, Yanchao; Li, Jiajing; Huo, Zihan; Liu, Bingxiang; Ma, Changming (Frontiers in Plant Science, 2022)
To investigate the response mechanism and salt tolerance threshold of three willow seedlings (Salix matsudana、 Salix gordejevii、 Salix linearistipularis), the absorption, transport and distribution of salt ions (Na+、K+、Ca2+) were studied under hydroponic conditions with different salt concentrations (CK、171mm、342mm、513mm、684mm) and treatment times (1 d、3 d、5 d、8 d、11 d、15 d). Salix linearistipularis has the weakest ability to maintain its apparent shape, while Salix matsudana has the strongest ability. The three plants have a certain Na+ interception ability, and the interception abilities of Salix matsudana and Salix gordejevii are higher than that of Salix linearistipularis. The leaf SAK, Na of Salix linearistipularis were higher than those of Salix matsudana and Salix gordejevii. The leaf selection ability was the highest, and the selection ability of the root system was the lowest in Salix linearistipularis. The long-term low salt concentration and the short-term high salt concentration can increase the root and leaf salinity. Salix matsudana grows more stably in a long-term high-salt stress environment, and Salix gordejevii grows stably in a short-term high-salt stress environment. However, Salix linearistipularis is more suitable for planting as an indicative plant because of its sensitivity to salt stress. The root Na+ content of Salix matsudana and Salix gordejevii was 34.21 mg/g, which was the maximum root retention capacity.Once the accumulation of Na+ content in roots exceeds this value, the rejection capacity of roots is broken through, and the selective ion absorption capacity will rapidly become weak , which easily leads to the death of plants.